THE ROLE OF MARKET VALUATION MODELS IN INVESTMENT DECISION-MAKING PROCESSES - Saković, Dušan; Ilić, Miloš (International Journal of Economic Practice and Policy, 2019)
The ground floor for deciding on the purchase or sale of shares or entire enterprises, recapitalization and other investment transactions are obtained in two basic understandings of value, the market price and the intrinsic value of companies. The price of shares or companies as a whole is the result of the supply and demand relationship and as such can be determined if there is an active market. On perfectly efficient markets, stock prices should match its intrinsic value. The intrinsic value is determined in the valuation process that requires the application of the selected valuation models. Market valuation models, on the one hand, rely on traditional models of valuation, while on the other hand they involve in valuation process information and tendencies from the market. The aim of this paper is to examine the role of these models in investment decision-making processes.